The Association Between Depressive Symptoms and Sarcopenia Among Community-Dwelling Older Adults: A Cross-Sectional Study - Zhang HY (Journal of Multidisciplinary Healthcare, 2022)
Hai Yan Zhang,1 Mei Chan Chong,1 Maw Pin Tan,2 Yan Piaw Chua,3 Jin Hua Zhang4 1Department of Nursing Science, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia; 2Department of Medicine, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia; 3Department of Mathematics and Science Education, Faculty of Education, University of Malaya, Kuala Lumpur, Malaysia; 4Faculty of Nursing, Xin Xiang Medical University, Xin Xiang City, People’s Republic of ChinaCorrespondence: Mei Chan Chong, Department of Nursing Science, Faculty of Medicine, University of Malaya, Kuala Lumpur, 50603, Malaysia, Tel +603-79492806, Email mcchong@um.edu.my Jin Hua Zhang, Faculty of Nursing, Xin Xiang Medical University, Xin Xiang City, 453000, People’s Republic of China, Tel +86-13837328062, Email zjh.warm@163.comPurpose: To evaluate the relationship between depressive symptoms and sarcopenia among older adults.Materials and Methods: This is a cross-sectional study. A total of 700 community-dwelling older persons enrolled in this study. Sarcopenia is defined according to the Asian Working Group for Sarcopenia 2019 (AWGS 2019). The bioelectrical impedance analysis assessed muscle mass while a digital dynamometer quantified muscle strength. Furthermore, a 6-meter gait speed test measured physical performance. The Geriatric Depression Scale (GDS-30) screened for depressive symptoms. Data collected include those of socio-demographic, lifestyle, and comorbidity.Results: The sample comprised 700 participants (455 women) with a mean age of 70.4± 6.8 years. 21.5% had sarcopenia, among them, 5.6% at severe stage, while depressive symptoms were present in 8.1% (57/700). After adjusting for the potential confounders of age, sex, marital status, living status, hypertension, body mass index, and physical activity, the depressive symptoms that were found were not associated with sarcopenia but, instead, low gait speed. However, severe sarcopenia significantly impacted the risk of depressive symptoms, particularly in females.Conclusion: Depressive symptoms are not associated with sarcopenia, but severe sarcopenia increases the risk of depressive symptoms in females, according to updated AWGS 2019 criteria. Gait speed is independently associated with depressive symptoms. The finding highlights that older people with sarcopenia should be screened for depressive symptoms, especially females. Future studies should evaluate the value of gait speed interventions for depressive symptoms among older adults.Keywords: depressive symptoms, sarcopenia, older people